The Rhetoric of a Corporate Job: from Enthusiasm to Desperation Decisions and Patterns of Staying and Leaving: Array - Marinescu, Alina Petra (Acta Universitatis Danubius. Communicatio, 2020)
My main research interest concerned the decisional processes of corporate employees when leaving their company, as they appear in retrospective accounts. I used discursive analysis of interview accounts to inquire into relationships between organizational identities and personal identities, and their shifting career dynamics. I studied how people construct their professional quests by investigating the discursive structure of the accounts involved in their professional stories. At the same time, I tried to figure out how people deal with their corporate and personal nested identities over time, presenting ‘corporations’ both as working environments and moral actors. I aimed to explain how people make use of various constructs of ‘corporation’ as scaffold for their stories and as interpretive frame for their professional and personal worlds. My analysis was grounded on a constructivist approach and sensible to the interviewees’ work of self-presentation. I also paid attention to the interactions people talk about and to the cultural resources they used in conversation. I favoured a narrative analytical perspective, given that respondents often presented their decisional processes in story-like form. Moreover, I took gender into consideration as a possible source of discursive patterns. As a research method, I used focused narrative interviews. I conducted 10 focused interviews with actual and former employees from different industries: media, IT and pharmaceuticals. My research work to date indicates that various types of narrative patterns emerge when interviewees recollect their working experiences. The most salient refers to a sequence of emotions presented in discourse, from enthusiasm to desperation. As a rule, the ‘corporation’ is constructed as an either good or a reluctant working environment depending on the moment of the story. Corporations on the whole gradually become personified, in later stages of the disengagement narrative, becoming important characters in employee’s stories. Agency is embedded in the organization and quickens the alienation process people go through.